rRNA and tRNA bridges to neuronal homeostasis in health and disease - Tuorto, Francesca; Parlato, Rosanna (Journal of molecular biology, 2019)
Dysregulation of protein translation is emerging as a unifying mechanism in the pathogenesis of many neuronal disorders. Ribosomal RNA (rRNA) and transfer RNA (tRNA) are structural molecules that have complementary and coordinated functions in protein synthesis. Defects in both rRNAs and tRNAs have been described in mammalian brain development, neurological syndromes, and neurodegeneration. In this review, we present the molecular mechanisms that link aberrant rRNA and tRNA transcription, processing and modifications to translation deficits, and neuropathogenesis. We also discuss the interdependence of rRNA and tRNA biosynthesis and how their metabolism brings together proteotoxic stress and impaired neuronal homeostasis.